COVID-19 and myocarditis: trends, clinical characteristics, and future directions - Abumayyaleh, Mohammad S. A.; Schupp, Tobias; Behnes, Michael; El-Battrawy, Ibrahim; Hamdani, Nazha; Akın, Ibrahim (Journal of Clinical Medicine, 2025)
Summary: COVID-19, caused by SARS-CoV-2, has been associated with a range of cardiovascular complications, including myocarditis. This review aims to systematically present the clinical manifestations, underlying pathophysiological mechanisms, diagnostic approaches, and management strategies for both COVID-19-associated myocarditis and myocarditis related to SARS-CoV-2 vaccination. We conducted a literature search using the PubMed database, covering studies published up to early 2024. Search terms included combinations of “COVID-19”, “Coronavirus”, “SARS-CoV-2”, and/or “vaccination” with “cardiac injury”, “cardiac inflammation”, “myocarditis”. The reported prevalence of COVID-19-associated myocarditis varies between 2.3% and 5.0%, though myocardial injury is more frequently observed than confirmed myocarditis. Pathophysiological mechanisms include direct viral damage, immune-mediated injury, and molecular mimicry. Clinically, patients may present with chest pain, dyspnea, and fever. Diagnostic workup includes electrocardiography (ECG), troponin measurement, echocardiography, cardiac magnetic resonance imaging (cMRI), and in selected cases, endomyocardial biopsy (EMB). The management and disposition of COVID-19-associated myocarditis varies according to severity, especially to allow targeted treatment of complications. Glucocorticoids are a mainstay of treatment in severe cases. Myocarditis following SARS-CoV-2 vaccination is rare, more frequently reported in males under 30 years, and is generally associated with a favorable prognosis. Despite this, the benefits of vaccination continue to outweigh the risks. COVID-19 is associated with an increased risk of heart failure and other cardiovascular complications, underlining the importance of long-term follow-up and preventive strategies. Further research is needed to better understand the pathogenesis and optimal management of myocarditis in the context of COVID-19, with the goal of developing evidence-based therapeutic algorithms.